Enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline via Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Kamble, Rohit B.; Suryavanshi, Gurunath M. (Tetrahedron Letters, 2015)
An enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline has been achieved in high optical purity (98% ee) from readily available 1,4-butanediol. The synthesis strategy employs a Keck allylation, CBS reduction, and Wacker oxidation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: CBS reduction; Keck allylation; Pyrrolidines; Wacker oxidation

AgNO3-Catalysed intramolecular cyclization: access to functionalized cyclopentanones and spiro-cyclopentanones - Bhoite, Shubhangi P.; Bansode, Ajay H.; Burate, Pralhad A.; Suryayanshi, Gurunath (Asian Journal of Organic Chemistry, 2019)
An efficient AgNO3-catalysed method has been developed for the synthesis of functionalized cyclopentanones and spiro-cyclopentanones through intramolecular cyclization between ynones and cyanoacrylate/aryl/alkylidene malononitrile using DBU as a base. Easy availability of starting materials and mild reaction conditions makes this protocol more feasible over previously reported methods. The functionalized cyclopentanones and spiro-cyclopentanones were synthesized in good to excellent yields with a broad substrate scope.

Radical rearrangement of aryl/alkylidene malononitriles via aza michael addition/decynoformylation/addition sequence: an access to alpha-aminonitriles and alpha-aminoamides - Bhoite, Shubhangi P.; Bansodes, Ajay H.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2020)
An efficient, safe, and environmentally friendly tertiary butyl hydrogen peroxide (TBHP)-mediated rearrangement of aryl/alkylidene malononitrile with anilines has been developed with in situ generation of HCN as the cyanide source for the synthesis of substituted alpha-aminonitriles and alpha-aminoamide. A diverse set of alpha-aminonitriles and alpha-aminoamides was efficiently synthesized in good to excellent yields. This method features a broad substrate scope and good functional group tolerance, and the in situ-generated HCN bypasses the use of an external cyanide source.

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species

Enantioselective synthesis of (+)-Sedridine, (-)-Allosedridine and their N-Methyl analogs via Maruoka-Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Suryavanshi, Gurunath (Natural Product Research, 2023)
A simple synthetic approach has been developed for the enantioselective total synthesis of (+)-Sedridine, (-)-Allosedridine and their analogs such as (+)-N- Methyl Sedridine and (-)-N-Methylallosedridine. The synthesis was achieved by using commercially available starting materials via Maruoka-Keck allylation, Wacker oxidation, and CBS reduction. The synthetic root provides a good diastereomeric ratio and high yields.
Keywords: CBS reduction; Maruoka-Keck allylation; Piperidine; Wacker oxidation

Mitochondrial resilience and antioxidant defence against HIV-1: unveiling the power of Asparagus racemosus extracts and Shatavarin IV - Jadaun, Pratiksha; Harshithkumar, R.; Seniya, Chandrabhan; Gaikwad, Shraddha Y.; Bhoite, Shubhangi P.; Chandane-Tak, Madhuri; Borse, Swapnil; Chavan-Gautam, Preeti; Tillu, Girish; Mukherjee, Anupam (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: IN-SILICO; INHIBIT HIV-1